Determination of the MESEP Events of 2-9th April 2001 According to ERNE/SOHO - H. Fadhel, Aseel; A. Al-Sawad, Amjad; M. Abood, Kamal (Iraqi Journal of Science, 2026)
On 2-9th April 2001 the Energetic and Relativistic Nuclei and Electron (ERNE)instrument on the Solar and Heliospheric Observatory (SOHO) observed threegradual solar energetic particle (SEP) events separated by 9 hour and 7daysrespectively, in association with three effective solar flares and coronal massejections (CMEs).In this paper, a study of MESEP events was considered. As the definition of thisphenomenon suggested there might be many sources for each MESEP event. Thisevent has been examined in order to view the different sources that might relate tosuspected accelerator of the SEPs. A careful analysis for the spectra and associatedemission with such eruptions was made. Soft X-ray emission was observed by theGeostationary Operational Environment Satellite (GOES) was used to indicate theassociated solar flares, earth radio stations were used to determine the associatedradio emissions. While three instruments, beside (ERNE) were used from the SOHOsatellite, the Large Angle Spectrometric Coronagraph (LASCO) to follow theCMEs, the Extreme-ultraviolet Imaging Telescope (EIT) for observing the Mortonwaves to indicate the CME location and the Charge, Element, and Isotope AnalysisSystem CELIAS to indicate the shock waves caused by CMEs.